Comprehensive Study of Mukhapaka and its Modern Counterpart (AYUSHDHARA, 2023)
Oral hygiene is very important for everybody’s health. Mukhapaka (stomatitis) is the disease that spreads throughout the mouth. It is the inflammation of mucous membrane of lips, tongue, and cheek. It is common problems faced by all persons. Though, it may seem like a minor problem but it inhibits the daily activities. Stomatitis occurs due to hot, spicy and greasy foods, smoking, tobacco chewing, several drugs, infections, Vitamin B12 deficiency etc. Ayurveda has described four types of Mukhapaka: Vataja, Pittaja, Kaphaja and Raktaja. Different types of Mukhapaka have different types of symptoms. Pain relievers, mouth washes, lotions, corticosteroids, Vit. B12 are used to treat stomatitis. In present era, world is looking at Ayurveda for its valuable contribution in the treatment of any ailment. Sarvasara Mukharogas are named as Mukhapaka, as they diffusely spread in the Mukha (oral cavity).